The effectiveness of application of phosphorous and potassium solubilizing multifunctional microbes (Aspergillus costaricaensis and Staphylococcus pasteuri mutants) on maize growth - Desak Ketut Tristiana Sukmadewi; Iswandi Anas; Rahayu Widyastuti; Syaiful Anwar; Ania Citraresmini (Journal of Degraded and Mining Lands Management, 2021)
The use of phosphorus and potassium-solubilizing microbes as biofertilizers is an alternative method to increase the availability of phosphorus and potassium in soils. This study aimed to explore the effectiveness of phosphorus (P) and potassium (K)-solubilizing multifunctional microbes (Aspergillus costaricaensis and Staphylococcus pasteuri mutants) on maize growth. The stages of this study consisted of viability test of P and K solubilizing A. costaricaensis and S. pasteuri mutants in peat and effectiveness test of P and K solubilizing A. costaricaensis and S. pasteuri mutants on maize growth. The results showed that peat carriers could keep the fungi population stable until 18 weeks of storage times. While the bacteria at 6 and 8 weeks storage times showed a slight decrease and stable in the 10 to 12 weeks storage time. The addition of P and K-solubilizing multifunctional microbes could reduce the use of fertilizer up to 50% in the treatment with a combination of easily soluble P or K sources with not-easily soluble P or K sources, as well as a combination of treatments of not-easily soluble P and K sources. This tended to occur in the treatment with the addition of A. costaricaensis mutant.